Biologics in IgE-mediated food allergy: A systematic review and meta-analysis of interventional studies - Ulugbek B. Nurmatov, MSc, MPH, MD, PhD; Lucia Lo Scalzo, MD; Francesca Galletta, MD; Marianna Krasnenkova, MD, PhD; Stefania Arasi, MSc, MD, PhD; Ignacio J. Ansotegui, MD, PhD; Nara Tagiyeva-Milne, MD, MPH, PhD; Alessandro Fiocchi, MD (World Allergy Organization Journal)
Background and aims: IgE-mediated food allergy (FA) is a major healthcare problem, affecting millions of children and adults worldwide. FA management usually involves elimination diets; however, there is increasing interest in alternative strategies that enable individualized optimal approaches. Yet, there is little consensus on the optimal strategies for managing FA. This review aimed to evaluate the effectiveness and safety of biologics, including omalizumab (OMA), as monotherapy or in combination with oral immunotherapy (OIT), for FA management. Methods: A systematic review (SR) and meta-analysis (MA) was conducted, searching 10 international electronic databases (from their start to May 2024) for randomized controlled trials (RCTs) assessing biologics in FA patients. The outcomes were desensitization, increased tolerated dose of food allergens, sustained unresponsiveness, adverse events/reactions (ARs/AEs), quality of life (QoL) measures, immunological biomarkers, and cost-effectiveness. Data were pooled using random-effects model. The study quality was assessed by the Cochrane Risk of Bias. Results: We included 11 RCTs, 2 secondary reports from earlier RCTs and 2 US National Clinical Trials with 1010 participants in total. Nine RCTs were at low, 3 at moderate, and 1 at high risk of bias. Meta-analyses demonstrated that OMA significantly improved desensitization rates and increased food tolerance thresholds compared to placebo (risk ratio (RR) 2.035, 95% CI: 1.29 to 3.22 and RR 4.90, 95% CI 2.14 to 11.20, respectively.) OMA reduced the risk of food allergic reactions (RR 0.55, 95% CI 0.36 to 0.85) without significantly increasing skin (RR = 1.09, 95% CI 0.45 to 2.65) or other adverse or severe reactions. Immunologic outcomes showed decreased hypersensitivity, a lowered allergic and inflammatory response. QoL measures improved for patients and parents with multifood oral immunotherapy. However, no studies investigated the cost-effectiveness of biologics in FA management. Conclusions: Based on the existing literature and our SR and MA, OMA can be recommended for use in carefully selected patients with IgE-mediated food allergies as monotherapy. However, patient-specific factors need to be addressed to reduce the risk of food-induced allergic reactions. OMA in combination with oral immunotherapy is recommended for cow's milk allergy. For the other foods, it will be recommended based on the results of ongoing, large RCTs in the field of biologics for food allergy. In order to recommend a wider indication for use, more research is needed to evaluate optimal treatment durations, long-term outcomes, and cost-effectiveness.